The roles of brewers' spent grain derivatives in coconut-based yogurt-alternatives: Microstructural characteristic and the evaluation of physico-chemical properties during the storage - Naibaho Joncer; Butula Nika; Jonuzi Emir; Korzeniowska Małgorzata; Chodaczek Grzegorz; Yang Baoru (Elsevier, 2025)
Water soluble coconut extract (WSCE) was reported as a suitable matrix for probiotic delivery as yogurt alternatives. The study aimed to evaluate the roles of brewers' spent grain (BSG) derivatives in enhancing the properties of WSCE-based yogurt alternatives. BSG flour (BSGF) and 3 different protein extracts (BSGPs) including protein control (BSGP-C), protamex treatment (BSGP-P), and protamex combined with flavourzyme treatment (BSGP-PF) were incorporated in WSCE-based yogurt alternatives. Confocal laser scanning microscopy showed that BSGPs prepared with protease treatment generated less dense fat distribution and more homogenous globules compared to that in WSCE control yogurt. It also resulted in a softer, denser and more homogenous matrix. The modification in microstructural properties was aligned with differences in several functional groups including ⍺-glycosidic bond and hydroxyl groups from polysaccharides, aliphatic ethers and acid functional groups as well as aromatic hydrocarbons of lignin, amide I, acetyl groups and amide III. BSGF and BSGPs increased the mechanical properties, viscosity and modified flow behaviour properties demonstrating its ability in maintaining textural and gel formation. After 14 days of storage, maintenance in flow behaviour, syneresis and mechanical properties was identified. Furthermore, BSG derivatives enhanced lactic acid production up to 3 folds. In conclusion, BSG derivatives maintained the microstructure and gel formation, improved the properties of WSCE-based yogurt alternatives and preserved its behaviour during 14 days of storage.